2003
DOI: 10.1007/s00122-003-1526-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage maps of two apricot cultivars (Prunus armeniaca L.) compared with the almond Texas × peach Earlygold reference map for Prunus

Abstract: Several genetic linkage maps have been published in recent years on different Prunus species suggesting a high level of resemblance among the genomes of these species. One of these maps (Joobeur et al., Theor Appl Genet 97:1034-1041 [(1998); Aranzana et al., Theor Appl Genet 106:819-825 (2002b)] constructed from interspecific almond Texas x peach Earlygold F(2) progeny (TxE) was considered to be saturated. We selected 142 F(1) apricot hybrids obtained from a cross between P. armeniaca cvs. Polonais and Stark E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 37 publications
6
57
2
1
Order By: Relevance
“…Gao et al (2004) reported 1 to 18 alleles per locus for 24 Japanese apricot cultivars in China by SSR analysis, with an average value of 9.1. One to 9 alleles were obtained for 14 peach cultivars (Yamamoto et al 2002) and 3 to 12 alleles were identified for SSR analysis of 25 apricot cultivars (Lambert et al 2004). In flowering cherry, the number of alleles per locus ranged from 4 to 36 by SSR analysis of 144 cultivars (Ohta et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al (2004) reported 1 to 18 alleles per locus for 24 Japanese apricot cultivars in China by SSR analysis, with an average value of 9.1. One to 9 alleles were obtained for 14 peach cultivars (Yamamoto et al 2002) and 3 to 12 alleles were identified for SSR analysis of 25 apricot cultivars (Lambert et al 2004). In flowering cherry, the number of alleles per locus ranged from 4 to 36 by SSR analysis of 144 cultivars (Ohta et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic co-linearity and marker transferability has been demonstrated within members of the Rosaceae (Joobeur et al, 1998;Dirlewanger et al, 2004aDirlewanger et al, , 2004bLambert et al, 2004;Dondini et al, 2007;Olmstead et al, 2008;Clarke et al, 2009;Cabrera et al, 2009). In 2009, a set of onserved Rosaceae genebased sequences corresponding to single copy Arabidopsis genes was developed (Cabrera et al, 2009).…”
Section: A Conserved Molecular Markers Among Members Of the Rosaceaementioning
confidence: 99%
“…Many of these genetic markers have been developed along the years, and from an early phase many of them have been applied to the genus Prunus, starting with the construction of a genetic map for improving breeding selection in peach (Chaparro et al, 1994). At least three genetic linkage maps of apricot have been published already (Hurtado et al, 2002;Vilanova et al, 2003;Lambert et al, 2004). Apricot diversity and genetic relationships have been studied using isozymes (Byrne and Littleton, 1989;Badenes et al, 1996), restriction fragment length polymorphisms (RFLPs) (De Vicente et al, 1998), random amplified polymorphic DNA (RAPDs) (Badenes et al, 2000), amplified fragment length polymorphisms (AFLPs) (Hagen et al, 2002;Hurtado et al, 2002) and sequence characterised amplified regions (SCARs) (Mariniello et al, 2002).…”
Section: Introductionmentioning
confidence: 99%